Linking GIS and Remote Sensing Data to Study Vegetation Patterns - Lemenkova Polina (Zenodo, 2015)
The paper studies changes in land cover types in tundra landscapes during the past two decades. The study area is located in the Yamal Peninsula, north-central Russia. The main objective of this research is to analyze changes in vegetation distribution and land cover types over the area of Yamal Peninsula. Methodology of the work aims at technical application of the remote sensing and GIS tools for studies and includes georeferencing, creation of color composites, supervised classification. The research data includes Landsat scenes. P. Lemenkova. "Linking GIS and Remote Sensing Data to Study Vegetation Patterns". English and Russian. In: New Technologies of Knowledge-Intensive Engineering: Priorities of Development and Training. Proceedings of the 3rd International Scientific-Practical Conference (Kazan National Research Technical University n.a. A.N. Tupolev KNITU-KAI, Nov. 27, 2015). Ed. by O. Y. Gerasimova, E. L. Gunicheva, and G. S. Mullagayanova. Naberezhnye Chelny, Russia (Tatarstan): KNITU-KAI Press, 2015, pp. 174–178. doi:10.6084/m9.figshare.7210388.